2010
DOI: 10.1007/s12192-009-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin induces the expression of heme oxygenase-1 and superoxide dismutase 1, 2

Abstract: Lipocalin-2 (Lcn2, NGAL) is a member of the lipocalin super family with diverse function such as the induction of apoptosis, the suppression of bacterial growth, and modulation of inflammatory response. Much interest has recently been focused on the physiological/pathological role of the lipocalin-2 that is considered to be a novel protective factor against oxidative stress. However, its precise biological roles in this protection are not fully understood. In this report we intended to test the effect of lipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…We found that HO-1 decreased 24 h after glycerol treatment and remained decreased through 72 h and that suramin up-regulated renal HO-1 at 72 h after glycerol treatment. One possible explanation for this observation could involve NGAL, because NGAL was shown previously to confer a cytoprotective and survival benefit in response to diverse forms of cellular stress by inducing HO-1 (Mori et al, 2005;Schmidt-Ott et al, 2007;Bahmani et al, 2010;Johnson et al, 2010). Consistent with this idea, we …”
Section: Untreated E 72 H After Glycerol + Suramin D 72 H After Glysupporting
confidence: 88%
“…We found that HO-1 decreased 24 h after glycerol treatment and remained decreased through 72 h and that suramin up-regulated renal HO-1 at 72 h after glycerol treatment. One possible explanation for this observation could involve NGAL, because NGAL was shown previously to confer a cytoprotective and survival benefit in response to diverse forms of cellular stress by inducing HO-1 (Mori et al, 2005;Schmidt-Ott et al, 2007;Bahmani et al, 2010;Johnson et al, 2010). Consistent with this idea, we …”
Section: Untreated E 72 H After Glycerol + Suramin D 72 H After Glysupporting
confidence: 88%
“…It has also been reported that NGAL may play a role in renal adaptation to diabetes, probably as a defensive mechanism to mitigate tubular injury (Bolignano et al, 2009b). NGAL has also been reported to have antioxidant properties (Roudkenar et al, 2007(Roudkenar et al, , 2008(Roudkenar et al, , 2011Bahmani et al, 2010). Of interest, in our study, renal NGAL increased in diabetic rats, and suramin intervention further increased renal NGAL.…”
Section: Downloaded Fromsupporting
confidence: 64%
“…This suggests that neutrophils, the primary effectors of acute inflammatory response in the body, require NGAL to home in to the target organs (in this case the transplanted heart). The latter role is suggested from observations made in both Chinese hamster ovary (CHO) and human embryonic kidney (HEK) cells that an aberrant expression of 24p3/Ngal leads to a significant upregulation in the expression of the antioxidant enzymes superoxide dismutase (SOD) and heme oxygenase (HO) (Bahmani et al, 2010;Roudkenar et al, 2007;Roudkenar et al, 2008c;Roudkenar et al, 2008a;Roudkenar et al, 2008b). NGAL also appears to play a role in wound healing.…”
Section: Functions Of Ngalmentioning
confidence: 99%